Experiences in implementing European Language Portfolio (ELP) with Italian Foreign Language (FL) pupils in primary school: A teacher's perspective - Mardešić, Sandra (Array, 2012)
The aim of this paper is to present a case study about the implementation of ELP with primary school pupils, learning Italian as a second foreign language, from a teacher’s perspective. The research is based on the analyses of a teacher’s diary and work reports, video recordings of classroom activities, conversations with a teacher, group discussions at the regular meetings of the participants in the project, and field notes of the researcher. Our findings indicate that the implementation of ELP had many positive effects not only for the pupils and their learning of a foreign language, but also the stimulation of their teacher to reflect on her work and to search for ways of improvement. Even though there were certain difficulties and uncertainties about the use of ELP, due to the novelty of the instrument, this study confirms that they can be overcome over time, and that the usefulness of this new approach in foreign language teaching is increasing with experience. These conclusions are comparable with other research findings, where other types of portfolios have been implemented such as European Portfolio for Student Teachers of Languages.